Differential Phenotypes in Perivascular Adipose Tissue Surrounding the Internal Thoracic Artery and Diseased Coronary Artery. Issue 2 (22nd January 2019) - Numaguchi, Ryosuke; Furuhashi, Masato; Matsumoto, Megumi; Sato, Hiroshi; Yanase, Yosuke; Kuroda, Yosuke; Harada, Ryo; Ito, Toshiro; Higashiura, Yukimura; Koyama, Masayuki; Tanaka, Marenao; Moniwa, Norihito; et al.
Abstract : Background: Perivascular adipose tissue (PVAT) is causally associated with vascular function and the pathogenesis of vascular disease in association with metabolically driven chronic inflammation called metaflammation. However, the difference in PVAT surrounding the coronary artery (CA‐PVAT) and that surrounding the internal thoracic artery (ITA‐PVAT), a vessel resistant to atherosclerosis, remains unclear. Herein, we investigated whether CA‐PVAT, ITA‐PVAT, and subcutaneous adipose tissue (SCAT) have distinct phenotypes. Methods and Results: Fat pads were sampled from 44 patients (men/women, 36:8; age, 67±13 years) with CA disease who underwent elective CA bypass grafting. Adipocyte size in ITA‐PVAT and that in CA‐PVAT were significantly smaller than that in SCAT. A greater extent of fibrosis and increased gene expression levels of fibrosis‐related molecules were observed in CA‐PVAT than those in SCAT and those in ITA‐PVAT. CA‐PVAT exhibited more pronounced metaflammation, as indicated by a significantly larger extent of CD68‐positive and CD11c‐positive M1 macrophages, a lower ratio of CD206‐positive M2 to CD11c‐positive M1 macrophages, a lower gene expression level of adiponectin, and higher gene expression levels of inflammatory cytokines and inflammasome‐ and endoplasmic reticulum stress–related molecules, than did ITA‐PVAT and SCAT. Expression patterns of adipocyte developmental and pattern‐forming genes were totally different among SCAT, ITA‐PVAT, and CA‐PVAT. Conclusions: The phenotype of ITA‐PVAT is closer to that of SCAT than that of CA‐PVAT, which may result from inherent differences in adipocytes. ITA‐PVAT appears to be protected from metaflammation and consecutive adipose tissue remodeling, which may contribute to the decreased atherosclerotic plaque burden in the ITA.